Pulmonary manifestations in the initial phase of schistosomiasis mansoni Alterações pulmonares da fase inicial da esquistossomose mansoni - Manoel Otávio C. Rocha; Regina Lunardi Rocha; Ênio Roberto P. Pedroso; Dirceu B. Greco; Cid Sérgio Ferreira; José Roberto Lambertucci; Naftale Katz; Roberto S Rocha; Dilermando F. Rezende; Jayme Neves (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
The clinical and radiological pulmonary manifestations in the initial phase of schistosomiasis mansoni were studied in thirty previously healthy individuals who were simultaneously infected. The findings were compared with those concerning a control group and related to possible pathogenetic factors. The respiratory manifestations were of light or of moderate intensity, the dry cough being the most common symptom. The significant radiological alterations were: thickening of bronchial walls and beaded micronodulation, predominantly localized in the lower pulmonary fields. It was observed significant association between wheezing and IgE levels, estimated by the area of immediate intradermal reaction, as well as between the number of blood eosinophils and the occurrence of radiological changes. Moreover, there was correlation between the worm burden and the presence of wheezing, thoracic pain and beaded micronodulation. Thus, the clinical and radiological pulmonary manifestations described are significant part of the initial phase of schistosomiasis mansoni and present the worm burden, eosinophilia and levels of IgE as probable pathogenetic factors. Foram estudadas as alterações clínicas e radiológicas pulmonares da fase inicial da esquistossomose mansoni em 30 indivíduos previamente sadios, que se infectaram simultaneamente. Os achados foram comparados aos de um grupo - controle e relacionados a possíveis fatores patogenéticos como carga parasitária, eosinofilia sangüínea e área de reação intradérmica imediata, esta como estimativa de IgE ligada a mastócito. As manifestações pulmonares foram de intensidade leve ou moderada, sendo a tosse seca o sintoma mais comum. As alterações radiológicas significativas constaram de espessamento de paredes brônquicas, micronodulação em rosário e micronodulação esparsa, localizadas predominantemente nas porções inferiores dos campos pulmonares. Verificou-se associação significativa de sibilos e área da reação intradérmica imediata, bem como entre o número de eosinófilos ...